2013
DOI: 10.1007/s13762-012-0174-z
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption kinetics of herbicide paraquat in aqueous solution onto a low-cost adsorbent, swine-manure-derived biochar

Abstract: Biochars have received increasing attention in recent years because of their significant properties such as carbon sequestration, soil fertility, and contaminant immobilization. In this work, the adsorptive removal of paraquat (1,1 0 -dimethyl-4,4 0 -dipyridinium chloride, one of the most widely used herbicides) from aqueous solution onto the swine-manure-derived biochar has been studied at 25°C in a batch adsorption system. The adsorption rate has been investigated under the controlled process parameters incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(31 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…Subsequently, increase in adsorbent concentration leads to the increase in total amount of active sites which improved the efficiency the removal of the total trace metals. Similarly, Tsai and Chen [83] reported that the number of adsorption sites increased in line with the increase in dosage of adsorbents (that is 0.10 to 0.30 g/L). Nonetheless, biochar produced from agricultural waste and other feedstock can shows adsorption efficiency that decreases as its mass increases.…”
Section: Dosage Of Biochar Adsorbentmentioning
confidence: 75%
“…Subsequently, increase in adsorbent concentration leads to the increase in total amount of active sites which improved the efficiency the removal of the total trace metals. Similarly, Tsai and Chen [83] reported that the number of adsorption sites increased in line with the increase in dosage of adsorbents (that is 0.10 to 0.30 g/L). Nonetheless, biochar produced from agricultural waste and other feedstock can shows adsorption efficiency that decreases as its mass increases.…”
Section: Dosage Of Biochar Adsorbentmentioning
confidence: 75%
“…Generally, the amount of sorption sites and surface area increased with the increment of applied sorbent. The research of Tsai and Chen (2013) showed that the residual equilibrium concentration of paraquat, a type of cation organic herbicide, was lowered in water solution with the increment of pig-manure biochar application. Graber et al (2011) indicated that the dosage of soil fumigant 1,3-dichloropropene for nematodes should be doubled to reach full activity when the soil is amended with biochar of 26 t ha −1 .…”
Section: The No3mentioning
confidence: 99%
“…The potential for biochar derived from greenwaste has been assessed specifically for triazine based herbicides [12]. The potential for biochar derived from pig manure has been assessed for the herbicide paraquat by [13] and for carbaryl plus atrazine by [14]. Deep percolation of pesticides leads to long term pollution of groundwater resources and represents a new area which needs to be addressed.…”
Section: Water Remediation Using Porous Biochar Geostructuresmentioning
confidence: 99%